Protocol for Extreme Low Latency M2M Communication Networks - Shamsudin, Rahim Karim (2019)
As technology evolves, more Machine to Machine (M2M) deployments and mission critical services are expected to grow massively, generating new and diverse forms of data traffic, posing unprecedented challenges in requirements such as delay, reliability, energy consumption and scalability. This new paradigm vindicates a new set of stringent requirements that the current mobile networks do not support. A new generation of mobile networks is needed to attend to this innovative services and requirements - the The fifth generation of mobile networks (5G) networks. Specifically, achieving ultra-reliable low latency communication for machine to machine networks represents a major challenge, that requires a new approach to the design of the Physical (PHY) and Medium Access Control (MAC) layer to provide these novel services and handle the new heterogeneous environment in 5G. The current LTE Advanced (LTE-A) radio access network orthogonality and synchronization requirements are obstacles for this new 5G architecture, since devices in M2M generate bursty and sporadic traffic, and therefore should not be obliged to follow the synchronization of the LTE-A PHY layer. A non-orthogonal access scheme is required, that enables asynchronous access and that does not degrade the spectrum. This dissertation addresses the requirements of URLLC M2M traffic at the MAC layer. It proposes an extension of the M2M H-NDMA protocol for a multi base station scenario and a power control scheme to adapt the protocol to the requirements of URLLC. The system and power control schemes performance and the introduction of more base stations are analyzed in a system level simulator developed in MATLAB, which implements the MAC protocol and applies the power control algorithm. Results showed that with the increase in the number of base stations, delay can be significantly reduced and the protocol supports more devices without compromising delay or reliability bounds for Ultra-Reliable and Low Latency Communication (URLLC), while also increasing the throughput. The extension of the protocol will enable the study of different power control algorithms for more complex scenarios and access schemes that combine asynchronous and synchronous access.